Fenomena Kedwibahasaan pada Anak Usia Sekolah Dasar: Studi Etnografi di Lingkungan Multikultural - M. Isnaini; Eka Putri Saskiatun Nabillah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study examines the phenomenon of bilingualism among elementary school children through an ethnographic study conducted in a multicultural environment, employing a sociolinguistic theoretical framework. Sociolinguistics, as an interdisciplinary field that investigates language-related issues in relation to its use within society, provides a foundation for understanding the complexity of bilingualism among children. The study aims to explore the patterns of bilingualism in elementary school students and their implications for language education in multicultural contexts. The research adopts a qualitative approach using the ethnography of communication method to observe children’s language use across various social contexts. The ethnography of communication is selected as an approach to understand culturally diverse communities, enabling an in-depth analysis of social, situational, and cultural factors that influence language use. The findings reveal that children experience incipient bilingualism, which serves as the foundation for subsequent bilingual development. Bilingualism is not merely an individual phenomenon but also a group phenomenon, functioning as a means of intergroup communication and a marker of identity. The children demonstrate challenges in both interactive and transactional communication, reflecting the complexity of navigating between their first language (L1) and Bahasa Indonesia as a second language (L2). This study confirms the importance of sociolinguistics as a fundamental foundation for education at the elementary level. The findings highlight the urgency of developing sociolinguistic approaches in language teaching that accommodate the realities of bilingualism. The implementation of a sociolinguistic approach in language learning requires a paradigm that views linguistic diversity as an educational asset rather than a barrier. In conclusion, the study underscores that sociolinguistics constitutes a fundamental interdisciplinary foundation for developing effective language education in multicultural contexts. This research contributes to a deeper understanding of sociolinguistic issues and provides a descriptive account of the social conditions of communities in relation to their language use.